HUBUNGAN PERILAKU HIDUP BERSIH DAN SEHAT (PHBS) DENGAN INFEKSI SOIL TRANSMITTED HELMINTHS (STHs) PADA ANAK SD DI TIWOHO KECAMATAN WORI - Indra Elisabet Lalangpuling; Mouren Irene Yusuf; Desinta Samala Majampoh; Kevin Giovani Pascoal; Michael V.L. Tumbol; Suwarja Suwarja; Rosdiana Naibey (Klinikal Sains : Jurnal Analis Kesehatan, 2024)
One of the factors that causes Soil Transmitted Helminths infection (intestinal nematodes that are transmitted through soil) is Clean and Healthy Living Behavior (PHBS). STHs usually breed in tropical areas with high temperatures and humidity. The aim of this research was to find out whether STHs worm infection which was transmitted through soil in elementary school children in Tiwoho Village, Wori District was related to clean and healthy living behavior (PHBS). This type of research is descriptive with a sampling method, namely purposive sampling of 65 stool samples that meet the inclusion criteria. Stool samples were examined microscopically using the native method, flotation method and Baerman Test method. The Square test was used in data analysis to assess whether there was a relationship between PHBS and STHs worm infection. The results of this study show that there is a relationship between Clean and Healthy Living Behavior (PHBS) and STHs worm infection, especially the habit of washing hands with soap before eating and the habit of biting nails with a p value <0.005.